The Impact of Teacher Autonomy on Technology Skills Development among K-12 STEM Educators during the COVID-19 Pandemic - Yuanlu Niu; Yi-Jung Lee; Beixi Li (Adult Education Research Conference, 2024)
This study aims to explore factors that have affected teacher autonomy in professional development and its impact on the development of technology skills among K-12 STEM teachers during the COVID-19 pandemic.
Keywords: Teacher autonomy; technology skills; professional development; K-12 teachers; STEM education